Strategi Penyelenggaraan Pesantren Pada Masa ‎Pandemi Covid-19 di Pondok Tahfidz Yanbu’ul Qur’an ‎Menawan Kudus - Muttaqin, Zaenal (QUALITY, 2021)
The aims of this research is to find out what steps or actions were taken by the managers of ‎Pondok Tahfidz Yanbu'ul Qur'an Menawan Kudus in Implementation Islamic boarding ‎schools during the Covid-19 Pandemic. This research is use field research (field research) with ‎a qualitative approach in research method. Data collection techniques using observation, ‎interviews and documentation. Data processing uses triangulation both techniques, time, and ‎sources.‎ From the research process can be seen that in order to implement the operational ‎standards of a boarding school during this pandemic, Islamic boarding schools need to ‎prepare and fulfill many things, ranging from infrastructure, human resource management, ‎until operational management. All steps or actions taken by the manager are aimed at making ‎the implementation of the boarding school run well and meeting the existing health protocol ‎standards. Of course, this all requires the role and cooperation of all parties involved in it. ‎With this research, it is hoped that it will be able to become a consideration for Islamic ‎boarding schools in Indonesia in organizing learning that appropriate with health protocols ‎that have been determined by the government.‎